PERSEPSI MASYARAKAT MUSLIM TERHADAP KE”SYARIAH”AN BANK SYARIAH DI INDONESIA - Dewi Ayu Sartika Putri1, Ronald Rulindo, Hendri Tanjung (IQTISHADUNA, 2019)
Indonesia is a country with the largest muslim population in the world. According to StatisticsIndonesia (Badan Pusat Statistik, abbreviated as BPS), 87% of 258,7 million citizens ofIndonesia are muslim. Despite having 87% of Indonesian citizen as muslim, many muslims inIndonesia are still reluctant to choose sharia banking over conventional banking. One of themost prominent reason is the perception that sharia banking has not fully complied to theprinciple of sharia. Research has been conducted to prove such perception using logit methodwhich involved 200 respondents from Jakarta. The result shows that 66% of respondents whoare the customers of sharia bank are not convinced that sharia bank conforms to a high level ofsharia requirements or consistent with the principles of Islamic law (sharia). Furthermore, 65%of respondents who are the customers of sharia bank do not actually have much knowledgeabout sharia banking. Therefore, the perception that sharia banking has not fully been a shariacompliancesystem is based on the fact that many of sharia bank?s customers do not have muchknowledge about sharia banking. In addition, the result from logistic regression shows thatsubstantial understanding about Fiqh Muamalat and level of religiousity are two factors thatinfluenced the customers in their choice of sharia bank with percentage of 5% and 1%respectively.